The Influence of the Talking Stick Learning Model on the Motivation and Learning Outcomes of Class V Students at SD Negeri 88 Palembang - Finayanti, Dila; Hakim, Lukman; Rizhardi, Rury (Jurnal Pendidikan Amartha, 2024)
This research aims to determine whether there is an influence of using the Talking Stick learning model on the motivation and learning outcomes of class V students at SD Negeri 88 Palembang. This research is a quantitative type using a Quasi Experimental type of experimental research method with a Nonequivalent Control Group Design. The population of this study were all fifth grade students at SD Negeri 88 Palembang. The sample for this research was students in classes V.3 and V.4 with a total of 50 students. The sample selection technique used was proportional sampling. Data collection techniques in this research are questionnaires and tests. Data analysis used the Independent sample T-test. The results of this research show that the average posttest learning motivation score for the experimental class is 87.28 and the control class is 78.72, while the average posttest learning result for the experimental class is 86 and the control class is 71.20. The results of the t-test calculation of learning motivation obtained t_count= 6.591 ≥ t_tabel= 1.678 and the results of the calculation of learning outcomes obtained t_count= 4.714 ≥ t_tabel= 1.678 with a significance level = 0.05. Based on the research results, it can be concluded that there is a significant influence of the use of the Talking Stick learning model on the motivation and learning outcomes of class V students at SD Negeri 88 Palembang.